Modulation of Cd carriers by innovative nanocomposite (Ca+Mg) and Cd-resistance microbes (Bacillus pumilus): a mechanistic approach to enhance growth and yield of rice (Oryza sativa L.) - Ali, Muhammad Azhar; Nafees, Muhammad; Waseem, Muhammad; Alomrani, Sarah Owdah; Al-Ghanim, Khalid A.; Alshehri, Mohammed Ali; Zheng, Hao; Ali, Shafaqat; Li, Fengmin (Frontiers in Plant Science, 2024)
Cadmium (Cd) is a well-known pollutant in agricultural soil, affecting human health through the food chain. To combat this issue, Ca + Mg (25 mg L−1) nanocomposite and Bacillus pumilus, either alone or combined, were applied to rice plants under Cd (5 mg kg−1, 10 mg kg−1) contamination. In our study, growth and yield traits demonstrated the beneficial influence of Ca + Mg and B. pumilus application in improving rice defense mechanism by reducing Cd stress. Combined Ca + Mg and B. pumilus application increased SPAD (15), total chlorophyll (18), chlorophyll a (11), chlorophyll b (22), and carotenoids (21%) with Cd (10 mg kg−1), compared to the application alone. Combined Ca + Mg and B. pumilus application significantly regulated MDA (15), H2O2 (13), EL (10), and O2•– (24%) in shoots under Cd (10 mg kg−1), compared to the application alone. Cd (10 mg kg−1) increased the POD (22), SOD (21), APX (12), and CAT (13%) in shoots with combined Ca + Mg and B. pumilus application, compared to the application alone. Combined Ca + Mg and B. pumilus application significantly reduced Cd accumulation in roots (22), shoots (13), and grains (20%) under Cd (10 mg kg−1), compared to the application alone. Consequently, the combined application of Ca + Mg and B. pumilus is a sustainable solution to enhance crop production under Cd stress.